Anti cancer activity of rodent tuber (Thyphonium flagelliforme (lodd.) Blume on human breast cancer t47d cells - Arief Nurrochmad,; Endang Lukitaningsih,; Edy Meiyanto, (International Journal of Phytomedicine, 2011)
The incidence of breast cancer in developing countries showed an increase from year to year. The efforts of cancer prevention or treatment of the more important given the frequency of occurrence is quite high. Several studies have been focuses on natural products as agents of cancer chemoprevention and as co-chemotherapy agent against cancer. One of medicinal plant that is widely used as anticancer is rodent tuber (Thyphonium flagelliforme (Lodd.) Blume). In present study, we investigated the anticancer acitivty of rodent tuber extract (RTE) in vitro. Study of anti-proliferative conducted on human breast cancer primary T47D cells. Furthermore, the present study also investigated the molecular mechanisms of cell cycle arrest and induction of apoptosis. The study of rodent tuber as co-chemotherapy is determined by examining the effects on T47D and its combination with tamoxifen (TAM). The results showed the cytotoxic effects of RTE on T47D cells with IC50 value of 632 μg/mL. Low concentration RTE (below 250 ug/mL) are proliferative, while the concentration above 250 μg/mL indicated cytotoxic effect. Based on the calculation of Combination Index (CI), combination of RTE with TAM yielded a value above 10 indicated a strong antagonistic effect. In observation of apoptosis, low concentration of RTE (63 µg/mL) stimulate apoptosis better than high concentration of 250 μg/mL. However, the combination study with 5 nM TAM reduced the induction of apoptosis. Furthermore, the observation cell cycle arrest by flowcytometry, demonstrated that RTE 63 and 250 μg/mL increase the population of sub G1 phase respectively from 14.8% to 53.19 and 32.90%. These results suggest that RTE able to induce cell cycle to apoptosis, but low concentration of RTE more effective than high concentration. Similar to apoptosis observation, the combination of RTE and TAM also demonstrated the antagonistic effect by reducing the population of Sub-G1 RTE (63 μg/mL) and TAM 5 nM, respectively from 53.19% and 44.50% to 35.86%. All finding results of this study provide information that the use of rodent tuber extract (RTE) alone is better than the combination with TAM. In addition, the use of RTE together with TAM reduced the effectiveness of TAM in the treatment of breast cancer.